(untitled) (Cambridge, UK, 2001)
This collection analyzes the material practice behind the concept of mapping, a particular cognitive mode of gaining control over the world. Ranging widely across visual and textual artifacts implicated in the culture of mapping, from the literature of Shakespeare, Spenser, Marlowe and Jonson, to representations of body, city, nation and empire, it argues for a thorough reevaluation of the impact of cartography on the shaping of social and political identities in early modern Britain.
Keywords: English literature,Politics and literature,Cartography,Space and time in literature,Geography in literature,Maps in literature,Văn học Anh,Chính trị và Văn học,Khoa nghiên cứu bản đồ; History and criticism,History,History,Lịch sử và phê bình,Lịch sử,Lịch sử; Early modern, 1500-1700,16th - 17th century,16th - 17th century; Great Britain,Great Britain